Evaluation of microbial quality of the surface water of Hatirjheel in Dhaka City - Miah, Md Badsha; Majumder, Ahmad Kamruzzaman; Latifa, Gulshan Ara (Stamford Journal of Microbiology, 2017)
Microbiological health risks due to environmental pollution are major concerning issue in all over the world. In Bangladesh, almost all the major water bodies (lake/khal) particularly in the urban or semi-urban area have been suffering severely pollutions. Therefore if we manage to safe our surface water in and around the city, we can reduce the demand of ground water for the city dwellers by the proper use of these lakes and ponds. This study was conducted to evaluate the microbial condition of Hatirjheel water located in Dhaka City. The microbial analysis was performed to trace the presence of bacterial and other pathogens. In 5 samples, total viable bacteria and fungi were found up to 2.0×106 cfu/ml and 3.4×102 cfu/ml, respectively. Specific pathogens such as Klebsiella spp. (3.0×102 cfu/ml), Salmonella spp. (2.0×102 cfu/ml), Pseudomonas spp. (8.3×102 cfu/ml) and Vibrio spp. (6.0×102 cfu/ml.) were also isolated. The findings of the study revealed that the water of Hatirjheel might not safe for human health and also indicated that this water may vulnerable for diarrhea, dysentery, typhoid fever, shigellosis, salmonellosis, parasitic worm infection, hemolytic uremina syndrome etc. water-borne diseases. The poor water quality suggesting contamination of the lake water by domestic and industrial wastes and other anthropogenic activities. So it is important to control the pollution for proper use of this water in various household purposes. Stamford Journal of Microbiology, Vol.6(1) 2016: 30-33